2021
DOI: 10.28918/ijibec.v5i1.3611
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement Model of Successful Muslim Entrepreneur

Abstract: Approximately 1.4 billion of the world's population lives on less than USD 1 per day, and since 50% of the poorest people are in Muslim countries, the solution is to increase successful Muslim entrepreneurs. Hence, this study aims to create a conceptual model through a literature review and descriptive-qualitative approach. These were employed to determine the indicators of successful Muslim entrepreneurs and the expected factors required to provide a positive and significant effect. Meanwhile, four factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Gyimah et al (2020) suggested that SME business success can be measured by business growth and financial performance, while Lekovic and Maric (2015) noted that some entrepreneurs define success in terms of financial indicators, such as high return on investment and market share. Bahril et al (2021) identified three dimensions of business success indicators, which are business achievement or performance, financial performance, and non-financial performance. The study found a significant and positive relationship between the entrepreneurial intelligence quotient (EIQ) of the entrepreneurs and their business achievements (r=0.296) and non-financial achievements (r=0.194) at the 0.01 and 0.05 levels of significance, respectively.…”
Section: Entrepreneurs' Business Successmentioning
confidence: 99%
“…Gyimah et al (2020) suggested that SME business success can be measured by business growth and financial performance, while Lekovic and Maric (2015) noted that some entrepreneurs define success in terms of financial indicators, such as high return on investment and market share. Bahril et al (2021) identified three dimensions of business success indicators, which are business achievement or performance, financial performance, and non-financial performance. The study found a significant and positive relationship between the entrepreneurial intelligence quotient (EIQ) of the entrepreneurs and their business achievements (r=0.296) and non-financial achievements (r=0.194) at the 0.01 and 0.05 levels of significance, respectively.…”
Section: Entrepreneurs' Business Successmentioning
confidence: 99%
“…Realising the success of the halal industry is critical to contribute to the goals of sustainable development, particularly on poverty alleviation, zero hunger, responsible consumption, and better nutrition, especially in Muslim-majority countries and globally (Muhammad Ashfaq 2018). Moreover, in the long term, the success of the halal industry can lead to an increase in the number of Muslim entrepreneurs, which, in turn, will provide prosperity to countries with a majority Muslim population and a global community (Bahri, Ali, and Aslam 2021).…”
Section: Success Factorsmentioning
confidence: 99%
“…Therefore, the conceptual model remains structured based on the approach of Meredith (1993), namely description, explanation, and continuous testing. Some researchers have used this approach (Bahri et al 2021;Bonney and Jaber 2014;Kovács and Spens 2007). This is illustrated in the following standard research cycle.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…The business activities being carried out by the santri have been scheduled by the Islamic boarding school so as not to interfere with religious learning, which is the main focus of an Islamic boarding school curriculum. The santripreneur program is carried out according to the talents and interests of the students so that when they do business, they will feel fun because realizing the success of being Muslim entrepreneurs is essential and is an effort to contribute to the prosperity of the nation (Ali et al, 2021).…”
Section: Life Skills Learning Processmentioning
confidence: 99%